Quantum mechanics experiment involving photons - Tuteja, Amit (International Journal of Psychosocial Rehabilitation, 2021)
With varied impediment statures, the energy spectra of two electrons in low-lying invigorated states in an indirect quantum spot are analyzed. The screened electron-composed exertion is treated with a dielectric work, and the affiliation energy for various spots is not entirely set in stone. The two-electron issue is similarly tended to as a colossal one-body issue. It is seen that as (I) affiliation impacts are fundamental for more unassuming spots; (ii) spatial ward screening limit doesn't cause clear changes in restricting energies; (iii) the impacts of obstruction stature are calculable on imprisonment but have no effect on electron relationship energy, and (iv) the impact of restricting energy for more modest spots is generous with the incorporation of the relationship impact more than treated as one body issue